Study of a thermal dispersion in buildings and advantages of ceramic coatings for the reduction of energy expenditure. (November 2020) - Carlini, Maurizio; Castellucci, Sonia; Ceccarelli, Ilaria; Rotondo, Mirko; Mennuni, Andrea
Abstract: Energy consumption in buildings is due to the low efficiency of thermal and electrical systems and the high rate of thermal dispersion of the building envelope, defined as one or more layers of material that separate the internal environment from the external environment of a building. Their function is to protect the internal environment from external agents such as cold, heat, moisture, rain, hail, snow, wind, light, sources of noise pollution and, based on the criticality of the place, air pollution. To reduce energy consumption, it is therefore necessary to act primarily on the building envelope, which should be designed and constructed with the aim of guaranteeing thermo-hygrometric comfort and reducing energy consumption (and consequently CO2 emissions). This means the ability to meet certain performance requirements without significantly impacting energy consumption, such as maintaining the environmental temperature during the wintertime and a better thermal comfort during the summer period. Therefore, when designing a new building or renovating an existing housing unit, technologies and materials must be used to improve the energy performance of the building. This work demonstrates that with the addition of a ceramic slab as external coating, the heat losses decrease by 42% with respect to a traditional wall configuration without any thermal insulator installed. As for the existing houses already equipped with an internal insulation or a coat, the addition of the ceramic slab results in decreases in thermal variation of 31 and 40% for the internal thermal coat installation and a post construction ready-to-use insulation, respectively.